Answers

  • Brainly User
2014-09-13T10:34:58+05:30
2y³ + y² - 2y -1 = (2y³ + y²) - (2y +1)
                        = y²(2y + 1) - 1x(2y+1)
                        =(2y+1)(y² - 1)
                        = (2y+1)(y+1)(y-1)

Henve dividing (2y³ + y² - 2y -1) / (y+1)
                       =  (2y+1)(y+1)(y-1) / (y+1)
                       = (2y+1)(y-1)
0
2014-09-13T11:03:13+05:30
2y³ + y² - 2y -1
= (2y³ + y²) - (2y +1)
= y²(2y + 1) - 1x(2y+1)
=(2y+1)(y² - 1)
= (2y+1)(y+1)(y-1)
 Hence dividing, (2y³ + y² - 2y -1) / (y+1)
= (2y+1)(y+1)(y-1) / (y+1)
= (2y+1)(y-1)
0